2022
DOI: 10.1186/s12920-022-01407-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis identifies potential hub genes and crucial pathways in the pathogenesis of asthenozoospermia

Abstract: Background Asthenozoospermia is a troublesome disease experienced by men in their reproductive years, but its exact etiology remains unclear. To address this problem, this study aims to identify the hub genes and crucial pathways in asthenozoospermia. Methods We screened two Gene Expression Omnibus (GEO) datasets (GSE92578 and GSE22331) to extract the differentially expressed genes (DEGs) between normozoospermic and asthenozoospermic men using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Network pharmacology is employed to identify candidate targets and elucidate bioactive compound functions in disease treatment and bioinformatics analysis is instrumental in investigating complicated gene–disease relationships and regulatory mechanisms ( Wang et al, 2022 ). These approaches have deepened our understanding regarding the action mechanisms of drugs ( Zou et al, 2022 ), successfully revealing the multitargeted pharmacological roles of several compounds including Fumaria indica and the Phellodendron–Anemarrhena drug pair in hepatocellular carcinoma treatment ( Batool et al, 2022 ; Ruan et al, 2022 ). Similarly, Xia et al used bioinformatics and network pharmacology to determine the inhibition mechanism of luteolin on the proliferation and migration of glioblastoma cells through the key targets BIRC5 and CCNB1, which impacted the prognosis of patients with glioblastoma ( Xia Z. et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is employed to identify candidate targets and elucidate bioactive compound functions in disease treatment and bioinformatics analysis is instrumental in investigating complicated gene–disease relationships and regulatory mechanisms ( Wang et al, 2022 ). These approaches have deepened our understanding regarding the action mechanisms of drugs ( Zou et al, 2022 ), successfully revealing the multitargeted pharmacological roles of several compounds including Fumaria indica and the Phellodendron–Anemarrhena drug pair in hepatocellular carcinoma treatment ( Batool et al, 2022 ; Ruan et al, 2022 ). Similarly, Xia et al used bioinformatics and network pharmacology to determine the inhibition mechanism of luteolin on the proliferation and migration of glioblastoma cells through the key targets BIRC5 and CCNB1, which impacted the prognosis of patients with glioblastoma ( Xia Z. et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research has provided initial insights into the dysregulated competitive endogenous RNA (ceRNA) network in asthenozoospermia, highlighting the potential involvement of exosomal lncRNAs in the pathogenesis of this condition ( 13 ). Although previous bioinformatics analyses have identified potential key lncRNAs, miRNAs, hub genes, and crucial pathways associated with asthenozoospermia ( 14 16 ), there are still many unexplored molecular mechanisms and potential biomarkers that related to asthenozoospermia need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The feature selection techniques are categorized into Unsupervised, Supervised, and Semisupervised based on the input dataset 11 . Within supervised feature selection, there are three main fashions 12 : filter, wrapper, and embedded. Finding an adequate feature set and enhancing the performance of the classification model's interpretability are the primary objectives of all techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of studies focusing on identifying the best feature selection techniques for bulk RNA-Seq data to identify potential therapeutic molecular markers or targets and gain molecular insights into cancer diagnosis and treatment. Even though, current existing studies identified disease associated features or genes on traditional Bioinformatics based interpretation 12,13,14 .…”
Section: Introductionmentioning
confidence: 99%